Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1109/23.736518
|View full text |Cite
|
Sign up to set email alerts
|

Charge collection and radiation hardness of a SOI microdosimeter for medical and space applications

Abstract: The first results obtained using a SO1 device for microdosimetry applications are presented. Microbeam and broadbeam spectroscopy methods are used for determining minority carrier lifetime and radiation damage constants. A spectroscopy model is presented which includes the majority of effects that impact spectral resolution. Charge collection statistics were found to substantially affect spectral resolution. Lateral diffusion effects significantly complicate charge collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…In this case the mean chord length was governed mainly by central part of N+ region 10 10 m and applied bias, which determines the charge collection efficiency (CCE or ) in the lateral dimensions of the SV [25]. Increasing the geometrical size of SOI SV to 100 100 m (from the more typically used 30 30 m ) does not essentially change the mean chord length, as any increase in size is offset by a proportional reduction in average CCE.…”
Section: Method: Phantom and Detectorsmentioning
confidence: 99%
“…In this case the mean chord length was governed mainly by central part of N+ region 10 10 m and applied bias, which determines the charge collection efficiency (CCE or ) in the lateral dimensions of the SV [25]. Increasing the geometrical size of SOI SV to 100 100 m (from the more typically used 30 30 m ) does not essentially change the mean chord length, as any increase in size is offset by a proportional reduction in average CCE.…”
Section: Method: Phantom and Detectorsmentioning
confidence: 99%
“…The charge collection efficiency as a function of position in the SOI device was determined using ion microprobe and alpha beam spectroscopy as previously reported [2], [5]. It was found that there was a small variation in charge collection efficiency of the diodes from regions nearest the diode junction (0.86) to regions furthest (0.79) the junction.…”
Section: Simulation Of Soi Microdosimeter In Fntmentioning
confidence: 99%
“…As previously reported [2], [3], [5], the SOI microdosimeter consists of an array of reversed biased, p-n junctions as illustrated in Figs. 1 and 2.…”
Section: B Soi Microdosimeter Descriptionmentioning
confidence: 99%
See 2 more Smart Citations